Plan de negocios para la creación de empresa de prestación de servicio público domiciliario de energía eléctrica mediante paneles solares, en la ciudad de santa marta (2023)
This business plan focuses on offering a renewable and sustainable energy alternative to homes and small businesses in the city of Santa Marta, Colombia. The company will provide its services to customers who are within its coverage area. It is intended to meet the growing demand for energy and reduce the renewable carbon footprint in the city and the region. In addition, the company seeks to offer a quality, reliable and safe service to its customers, with an affordable and transparent business model. This project uses a mixed investigative typology, since it carries out an analytical spectrum at a qualitative and quantitative level, making use of secondary tools for the formulation of the different methodological scenarios, and a primary tool for the recognition of sectoral scenarios. which the business faces. This research is part of the institutional line of Management of organizations.